BIBLICAL HEBREW: TEACHING AND LEARNING THE ALPHABET WITH AUDIO-VISUAL AIDS - Fasuba, Ayodeji Francis (International Online Journal of Education and Teaching, 2025)
Sound mastery of the Biblical Hebrew alphabet is required for proficiency in Biblical Hebrew. This study examined Biblical Hebrew: teaching and learning the alphabet with audio-visual aids. Alef-Bet-Song and video lectures on Biblical Hebrew alphabet downloaded from YouTube were integrated into the lessons and taught during instructional process. A Quasi-experimental research design (involving experimental and control groups) was adopted for the study. 100 level undergraduate CRS students in four universities from south-west Nigeria formed the sample for the study. Achievement Test in Biblical Hebrew alphabet (ATBHA) was utilised for data collection, while research hypotheses were analysed using t-test. Findings revealed that the integration of audio-visual resources within the lecture format has a statistically significant effect on students' learning outcomes. In addition, it was affirmed that there is significant difference in the retention level of students exposed to Biblical Hebrew alphabet utilising lecture method complemented with audio-visuals after treatment. It was therefore recommended that Lecturers of Biblical Hebrew should adopt lecture method complemented with audio-visual aids during instructional process of Biblical Hebrew alphabet, and that they should align themselves with the trend of integrating available technologies, social media platforms, and audio-visual aids into their lessons for improved learning outcomes.